2003
DOI: 10.1046/j.1442-2042.2003.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 74 cases of seminoma treated with radiotherapy

Abstract: Background : Standard post-orchiectomy radiotherapy (RT) is accepted as a standard management option for stage I seminoma. Methods : Retrospective evaluation of 74 patients with stage I seminoma was performed according to the Royal Marsden staging system. All of the patients underwent RT in the Radiation Oncology Department of Gülhane Military Medical Academy between 1974 and 1995. The median age of patients was 27 years (range, 20-56). Radiotherapy was applied to all of the patients after orchiectomy for adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Seminoma may also be considered as it is the most commonly encountered tumour in the testis 24. However, the lack of PAS immunoreactivity and the absence of clear and vacuolated cytoplasm excluded the possibility of seminoma 25 26…”
Section: Discussionmentioning
confidence: 99%
“…Seminoma may also be considered as it is the most commonly encountered tumour in the testis 24. However, the lack of PAS immunoreactivity and the absence of clear and vacuolated cytoplasm excluded the possibility of seminoma 25 26…”
Section: Discussionmentioning
confidence: 99%
“…Although seminomas are usually early-stage tumors and curable with standard treatments, chemotherapy after surgery is preferred for non-seminomatous tumors. Güden et al (12) reported that five-year survival and five-year disease-free survival rates were 98.6% and 90.54%, respectively, in 74 stage I seminomas. According to the World Health Organization toxicity scale, grade I and II enteritis were reported as 9.4% and 5.4% while grade I and II nausea and vomiting were observed in 36.4% and 5.4% of the patients, respectively (12).…”
Section: Discussionmentioning
confidence: 99%
“…Güden et al (12) reported that five-year survival and five-year disease-free survival rates were 98.6% and 90.54%, respectively, in 74 stage I seminomas. According to the World Health Organization toxicity scale, grade I and II enteritis were reported as 9.4% and 5.4% while grade I and II nausea and vomiting were observed in 36.4% and 5.4% of the patients, respectively (12). Radioiodine treatment is worth investigating as an alternative therapy for treatment-resistant tumors or for patients who cannot have radiotherapy or chemotherapy because of severe side effects.…”
Section: Discussionmentioning
confidence: 99%